Anisotropic, strong, self-adhesive and strain-sensitive hydrogels enabled by magnetically-oriented cellulose/polydopamine nanocomposites. (15th January 2022) - Yan, Guihua; He, Shuaiming; Chen, Gaofeng; Tang, Xing; Sun, Yong; Xu, Feng; Zeng, Xianhai; Lin, Lu
Abstract: Recently, great efforts have been devoted to developing conductive adhesive hydrogels to meet the needs of various applications. However, grand challenges remain in achieving anisotropic hydrogels simultaneously featuring multiple properties using natural polymers and renewable resources. Here, a cellulose-based conductive hydrogel with strong, ultrastretchable, and adhesive properties is prepared via a simple magnetic field-induced strategy. This strategy involves the formation of a suspension mixture with well-oriented cellulose-polydopamine nanocomposites under magnetic fields, followed by rapid orientation via covalent crosslinking. The tensile strength of the oriented hydrogel in longitudinal direction is ~0.22 MPa, which is ~1.4 times higher than that in radial direction. Moreover, the hydrogel shows good cyclic loading-unloading ability, high conductivity (6.9 ± 0.6 S m −1 ), and strong adhesion (71 kPa). The hydrogel also shows significant anisotropic properties and made it a versatile platform for wearable sensors to monitor large and subtle human motion in the foreseeable future. Highlights: An anisotropic hydrogel is prepared from cellulose by Schiff base reaction. Magnetically-oriented cellulose/polydopamine composites are the key to the study. The sheet-like nanocomposites replace traditional nanoparticles or nanowires. The high level of alignment endows the hydrogel obvious anisotropic properties. The hydrogel also has good conductive and adhesive properties.